An Overview of Suicide Risk for Homeless Women at Pondok Social Surabaya: Case Study - Retno Ayu Astrini; Ike Herdiana (Universitas Muhammadiyah Sidoarjo, 2018)
This case study describes an interview on the risk of suicide to a homeless woman in a social lodge in Surabaya, referred to as YS, which shows the symptoms of suicidal tendencies. The interview assessment used is a structured interview guide from the NSW department of health (2010) about the risk of suicide in individuals. The results of the suicidal risk assessment interview on the subject of YS ie the subject has ever thought about committing suicide. The originator is related to the problem in the sticky figure, namely the family. Other triggers include neglect from close relatives, until finally the subject is entrusted to Liponsos. The subject explained that he had tried to kill himself and hurt himself in the early months of 2017. The subject had tried to wash his hands until his hands were bleeding. The subject also stabbed himself using a pin even today. The subject considered death a scary thing, but on the other hand the subject also felt awry. The subject claimed that he already had a plan to end his life, but he was confused because it was impossible to end his life in Liponsos, even though he thought that in Liponsos there were also residents who died. The dynamics of YS suicidal risk trends will be explained in this case study report.